Effects of Radiation Dose of Photon and Electron Beam Energies and Angles in Radiation Therapy - Khadka, Narendra; Neupane, Bijay Raj; Karki, Ram Sharan; Baniya, Smriti; Baniya, Hom Bahadur (Cognition, 2025)
This study explores the effects of varying radiation beam energy levels and angles on the doses administered to adjacent healthy tissues and tumors during cancer treatment. While electron beams are best suited for superficial tumors because of their shallow penetration depth, photon beams produced by linear accelerators are useful for deep-seated tumors. Radiation doses were measured at different angles with 6 MV and 15 MV photon beams at 0° and 60° and with 6 MeV, 12 MeV, and 15 MeV electron beams at 0° and 15°. The findings demonstrate that larger angles and higher energy produce higher doses at different positions in photon therapy. Energy levels in electron therapy have a greater effect on dose distribution than angles. Our linear regression model analysis found that energy level angles and dose measurements in photon therapy strongly correlate with high R2 scores (above 0.8). Substantial and inconsistent correlations were observed with electron therapy. Despite these variations, a positive correlation was seen between various dose measurements for both treatments. These results emphasize the significance of choosing the right angles and energy levels to maximize treatment efficacy and minimize harm to healthy tissues. The use of these treatment protocols in clinical settings is supported by comparing our results with international standards which guarantee safety and efficacy.